Improving Calendar Modeling Of Array Construction Typical Low-Rise Buildings By Flow Method - Yusupova Lobar Sidiqovna; Mirakhmedov Makhamadjon (The American Journal of Engineering and Technology, 2020)
Population growth, the compact location of villages and towns around cities, the creation of jobs on their territory makes the construction of affordable housing in rural areas relevant. In order to improve project management, in particular, to create a single platform that unites the efforts of construction participants and further reduce the cost of projects, a methodology has been proposed for developing a schedule for the construction of a complex consisting of an array of residential buildings, social infrastructure and linearly extended structures. The resulting schedule can be used to conclude contracts between construction participants and clarify financing schedules, start and end dates of stages, supply of material and technical resources to the construction site.